2018
DOI: 10.3389/fpubh.2018.00302
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-Led Diabetes Self-Management Education Improves Clinical Parameters in Ethiopia

Abstract: Background: Unlike in developed countries, the clinical effectiveness of diabetes self-management education (DSME) is not well-studied in the African context. Thus, this study sought to determine effects of DSME on clinical outcomes among type 2 diabetic (T2DM) patients in Ethiopia.Methods: Before-and-after controlled study design was employed, with random assignment of 116 T2DM adult patients to a nurse-led DSME group and 104 to a treatment-as-usual (comparison) group. A nurse-led DSME with six sessions suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(95 citation statements)
references
References 44 publications
5
85
1
2
Order By: Relevance
“…Unexpectedly, we failed to find that NLTM had a significant impact on the decrease of FBS levels during the 12-month follow-up period, which was not consistent with previous findings that community-based diabetes self-management education could cause a significant reduction in FBS levels 36,37. Although the result was not significant between groups, the mean of FBG did drop from 8.04 mmol/L to 7.84 mmol/L in the intervention arm; whereas the mean kept the same level from 8.13 mmol/L to 8.10 mmol/L in the control arm.…”
Section: Discussioncontrasting
confidence: 86%
“…Unexpectedly, we failed to find that NLTM had a significant impact on the decrease of FBS levels during the 12-month follow-up period, which was not consistent with previous findings that community-based diabetes self-management education could cause a significant reduction in FBS levels 36,37. Although the result was not significant between groups, the mean of FBG did drop from 8.04 mmol/L to 7.84 mmol/L in the intervention arm; whereas the mean kept the same level from 8.13 mmol/L to 8.10 mmol/L in the control arm.…”
Section: Discussioncontrasting
confidence: 86%
“…A study by Feng et al (2018) has shown that systolic blood pressure significantly decreased in diabetic Chinese patients, in intervention group after self-care education [92]. In a study conducted by Hailu et al (2018) in Ethiopia, diabetic patients in the intervention group received a significant reduction in FBS, systolic blood pressure and diastolic blood pressure in the control group after intervention [93]. This is in agreement with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the nature of our DSME intervention, we could not blind the data collectors or our study participants. Our adherence to the CONSORT flowchart has been explained in detail elsewhere 24…”
Section: Methodsmentioning
confidence: 99%
“…The multifaceted intervention consisted of three main elements: a) six educational sessions, each lasting for 1.5 hrs on average, focusing on basic diabetic knowledge and self-care behavior; b) a colorful, well-illustrated educational handbook and fliers adapted to the local context; and c) extensive and interactive discussions with peers and take-home activities. A detailed description of our DSME intervention is available elsewhere 24…”
Section: Methodsmentioning
confidence: 99%